La santé et la sécurité au travail des travailleurs immigrants à Montréal : résultats d’une enquête exploratoire - Sylvie Gravel; Laurence Boucheron; Michel Kane (Perspectives Interdisciplinaires sur le Travail et la Santé)
Immigrant workers have always made up a significant part of the blue-collar workforce in Montreal. These workers have to work to survive. Work is also their principal strategy for integration, and also one of the main reasons for emigrating. They agree to work in precarious conditions because of their own volatile economic situation, their difficulties with the languages of the host society, and the fact that they have no social or professional network of their own. Immigrant workers are usually unaware of their rights because they often come from countries that have few or no workplace safety standards. In response to a request from community groups supporting immigrant integration and assimilation into the workforce, and from organizations defending the victims of occupational accidents, the Montreal Public Health Department conducted an exploratory survey, the results of which are presented in this article. The survey was conducted from October 2000 to March 2001 with 17 key informants from community organizations, occupational health institutions and research centres. Semi-structured interviews were carried out in the workplace or by telephone, based on a sample of organizations selected because of their social mandate. The results show that public health and occupational safety agencies are not in a position to demonstrate the extent or severity of accidents among immigrant workers, since there are no epidemiological data to document either the situation of the workers or their immigration patterns. Moreover, the survey enabled us to outline the various viewpoints contributing to an analysis of the workers’ needs ; these contradictory viewpoints emerged not only from occupational health and safety agencies, but also from unions and community groups. Finally, the study allowed us to determine the pertinence of continuing our work on the factors that facilitate and limit access to compensation for immigrant workers who have suffered work injuries.